Thermal energy storage based on local eco-materials for concentrating solar power plants : case of CSP4africa pilot - (:unkn) unknown (My University, 2017)
Convinced of the interest and potential of natural materials and industrial waste, this thesis has contributed to the development of heat storage materials (TESM) for CSPs in West Africa. More specifically, this research focused on the valorization of laterite from Burkina Faso, the bottom ashes from the coal-fired power plants of SONICHAR in Niger, residues of calcium carbonate (lime) from the acetylene in Burkina Faso and the vegetable oil of Jatropha curcas from the company Belwet in Burkina Faso. The results of this study showed that Jatropha curcas oil can be considered as a viable alternative to conventional HTF and TESM for CSP operating at 210 °C. The materials elaborated from bottom ashes and laterites present a refractory character due to the presence of mullite and spinel. The addition of lime makes it possible to reduce the melting temperature while preserving the refractory and conductive character of the obtained phases. Due to their stabilities, and the absence of conflict of use, the obtained materials can be used as TESM in CSP at temperatures up to 900 °C.
Keywords: African Research